Foliar phloem infrastructure in support of photosynthesis - Adams, William W.; Cohu, Christopher M.; Muller, Onno; Demmig-Adams, Barbara (Frontiers in Plant Science, 2013)
Acclimatory adjustments of foliar minor loading veins in response to growth at different temperatures and light intensities are evaluated. These adjustments are related to their role in providing infrastructure for the export of photosynthetic products as a prerequisite for full acclimation of photosynthesis to the respective environmental conditions. Among winter-active apoplastic loaders, higher photosynthesis rates were associated with greater numbers of sieve elements per minor vein as well as an increased apparent total membrane area of cells involved in phloem loading (greater numbers of cells and/or greater cell wall invaginations). Among summer-active apoplastic loaders, higher photosynthesis rates were associated with increased vein density and, possibly, a greater number of sieve elements and companion cells per minor vein. Among symplastic loaders, minor loading vein architecture (number per vein and arrangement of cells) was apparently constrained, but higher photosynthesis rates were associated with higher foliar vein densities and larger intermediary cells (presumably providing a greater volume for enzymes involved in active raffinose sugar synthesis). Winter-active apoplastic loaders thus apparently place emphasis on adjustments of cell membrane area (presumably available for transport proteins active in loading of minor veins), while symplastic loaders apparently place emphasis on increasing the volume of cells in which their active loading step takes place. Presumably to accommodate a greater flux of photosynthate through the foliar veins, winter-active apoplastic loaders also have a higher number of sieve elements per minor loading vein, whereas symplastic loaders and summer-active apoplastic loaders have a higher total number of veins per leaf area. These latter adjustments in the vasculature (during leaf development) may also apply to the xylem (via greater numbers of tracheids per vein and/or greater vein density per leaf area) serving to